(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Expanding advanced innovation has revolutionized the life of individuals. In this digital world many countries are trying to initiate an E-voting system in regular election process. Researchers are looking forward for the innovative ideas for secure and user friendly system. Block chain is one of the novel concepts that come with number of features to develop E-services. By embracing block chain in the circulation of databases on e-casting ballot frameworks, one can decrease the duping wellsprings of database control. This venture intends to execute casting a ballot result utilizing block chain calculation from each place of decision. In proposed system we have chosen Block chain for its decentralized framework and Here in security and data integrity is mainly achieved by making use of Visual Cryptography (VC) concept. This VC technique comes in when user casts vote on an E-voting portal.